Mind the gap: role expectations and perceived performance of the EU in the South Caucasus. Issue 2 (4th March 2021) - Delcour, Laure; Wolczuk, Kataryna
ABSTRACT: This article focuses on how the European neighborhood policy is viewed in the three South Caucasus countries (Armenia, Georgia and Azerbaijan). We explore perceptions of the EU's role in the region and compare these perceptions with the EU's own role conceptions in the neighborhood. We use role theory as a theoretical framework, within which these perceptions can be analyzed and compared. We scrutinize the partner countries' perception of the EU as a driver of democratization and modernization, as well as their assessment of the degree to which the EU fulfills the role. Our findings indicate that the EU's role conception is indeed recognized and accepted by a majority of key actors in the South Caucasian countries. However, in the perceptions of South Caucasus actors the EU's role as a promoter of democratization and modernization is not mirrored by its role performance, as EU policies do not adequately address the domestic and regional contexts.